Defining the phenotype of FHF1 developmental and epileptic encephalopathy. (9th July 2020) - Trivisano, Marina; Ferretti, Alessandro; Bebin, Elizabeth; Huh, Linda; Lesca, Gaetan; Siekierska, Aleksandra; Takeguchi, Ryo; Carneiro, Maryline; De Palma, Luca; Guella, Ilaria; Haginoya, Kazuhiro; Shi, Ruo Ming; et al.
Abstract: Fibroblast growth‐factor homologous factor ( FHF1 ) gene variants have recently been associated with developmental and epileptic encephalopathy (DEE). FHF1 encodes a cytosolic protein that modulates neuronal sodium channel gating. We aim to refine the electroclinical phenotypic spectrum of patients with pathogenic FHF1 variants. We retrospectively collected clinical, genetic, neurophysiologic, and neuroimaging data of 17 patients with FHF1 ‐DEE. Sixteen patients had recurrent heterozygous FHF1 missense variants: 14 had the recurrent p.Arg114His variant and two had a novel likely pathogenic variant p.Gly112Ser. The p.Arg114His variant is associated with an earlier onset and more severe phenotype. One patient carried a chromosomal microduplication involving FHF1 . Twelve patients carried a de novo variant, five (29.5%) inherited from parents with gonadic or somatic mosaicism. Seizure onset was between 1 day and 41 months; in 76.5% it was within 30 days. Tonic seizures were the most frequent seizure type. Twelve patients (70.6%) had drug‐resistant epilepsy, 14 (82.3%) intellectual disability, and 11 (64.7%) behavioral disturbances. Brain magnetic resonance imaging (MRI) showed mild cerebral and/or cerebellar atrophy in nine patients (52.9%). Overall, our findings expand and refine the clinical, EEG, and imaging phenotype of patients with FHF1 ‐DEE, which is characterized by early onset epilepsy with tonic seizures, associated with moderate to severe ID and psychiatric features.